Influence of Career Self Efficacy, Gender Stereotyping and Career Self-Concept on Sex-Typed Career Choice of Senior High School Students - Amoah, Charles Agyei; Agyemang, Thomas; Adjei, Augustine; Agyemang (EdD), Samuel (International Journal of Scientific Research and Management (IJSRM), 2020)
This study examined the influence of Career Self-Efficacy, Gender Stereotyping and Career Self-Concept on Sex-Typed career choices of students in the Asante Akim North Municipality. The descriptive, survey design using the quantitative approach was adopted for the study. Eight hundred (800) final year Senior High School Students (five hundred) (500) males and three hundred (300) females from the Asante Akim North Municipality were selected for the study using opportunistic and purposive sampling methods. Data were analyzed using various analytical techniques including multiple regression and t-tests. Among the present study’ findings were that Career Self-Efficacy was found to have more influence on the students’ Choice of Sex-Typed Career than Gender Stereotyping and Career Self-Concept. The present findings also suggested that the female students chose significantly more female-dominated Careers than their male counterparts. Similarly, students from female-dominated families chose more female-denominated careers than those from male-dominated families. Among the recommendations was that since it was found that students in the present study appeared to sex-stereotype careers, more guidance and counselling co-ordinators should be trained in order to counsel students to choose career according to their abilities and not their sex. The findings are discussed in relation to pervious findings and recommendations made based on the present findings.